MEDICINAL FLORA OF THE VIDLIČ MOUNTAIN IN SERBIA - Marković, Marija; Stankov-Jovanović, Vesna; Smiljić, Mirjana (Bulletin of Natural Sciences Research, 2019)
A study of medicinal flora of the Vidlič mountain situated in southeastern Serbia was conducted. The presence of 264 plant species, that are considered official or used in folk medicine is recorded. An overview of medicinal plants is given in a systematic order. For each herb species, main medicinal substances which enter in its chemical composition are listed. An overview of plant parts which are curative and which families contain the highest numbers of medicinal species, are presented. A special review of species that contain toxic substances, as well as species that have become so rare in their natural habitats by irrational exploitation in nature that they have been declared protected and strictly protected taxa in the Republic of Serbia is given.
Keywords: Mt. Vidlič; Medicinal plants; Active ingredients; Protected species